2009
DOI: 10.1007/s00268-008-9890-4
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Laparoscopic Appendectomy During Pregnancy

Abstract: Laparoscopic appendectomy is safe and effective during pregnancy and is associated with good maternal and fetal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 38 publications
1
64
0
6
Order By: Relevance
“…The first described case of laparoscopic appendectomy was performed during the 8th week of pregnancy, followed thereafter with a 1990 case series of six patients averaging 16.3 weeks of gestation; each had no reported complications. Overall, when considering the effects of laparoscopic appendectomy on fetal outcomes, reported rates of fetal demise are low, ranging from 0 to 4.8 % [19,20,22,[30][31][32][33]. According to the CDC, the current rate of fetal loss surveying all pregnancies in the USA excluding elective abortions is 17 % [34].…”
Section: Discussionmentioning
confidence: 99%
“…The first described case of laparoscopic appendectomy was performed during the 8th week of pregnancy, followed thereafter with a 1990 case series of six patients averaging 16.3 weeks of gestation; each had no reported complications. Overall, when considering the effects of laparoscopic appendectomy on fetal outcomes, reported rates of fetal demise are low, ranging from 0 to 4.8 % [19,20,22,[30][31][32][33]. According to the CDC, the current rate of fetal loss surveying all pregnancies in the USA excluding elective abortions is 17 % [34].…”
Section: Discussionmentioning
confidence: 99%
“…3,[51][52][53][54][55][56][57][58][59][60][61][62] Although long-term data on the safety and efficacy of laparoscopic appendectomy during pregnancy are limited, meta-analyzes of observational studies, including a total of more than 500 laparoscopic appendectomies, have shown an increase in the fetal loss rate with this approach, when compared with open appendectomy. 63,64 In a 2012 meta-analysis (11 studies, 3,415 women, 599 in the laparoscopic and 2,816 in the open group), the total relative risk of fetal loss for laparoscopic appendectomy against open surgery in pregnant women was OR 1.91, 95% CI 1.31 to 2.77%.…”
mentioning
confidence: 99%
“…However, advocates of the laparoscopic approach have cited longterm studies that demonstrate its safety for the fetus and mother, independent of trimester, and relate complications to the degree of underlying severity of appendicitis [93,[95][96][97][98]. Several retrospective reviews have shown a lack of complications in newborns, including adequate weight for gestation age, well-being at birth [99][100][101] and one prospective paper showing no association with developmental delays of motor, sensory or social skills by 3 years of age [1].…”
Section: Controversies In Surgical Managementmentioning
confidence: 99%